MOTHER'S PARENTING PRACTICES IN DEVELOPING SELF-CONFIDENCE OF BROKEN HOME CHILDREN IN ELEMENTARY SCHOOL - Riginia Tri Meitasari; Reza Rachmadtullah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research is based on the family as the smallest social unit and is the first and main educational institution for children before children receive formal education at school. However, the desire to have a complete family, sometimes does not always come true due to various factors, for example a breakdown in the household (broken home). Every day children will see the attitudes and behavior shown by their parents so that this will indirectly be absorbed and become a habit for their children. Talking about parenting patterns is very important in a family. With parental parenting patterns, social interactions can occur which are useful for introducing children to the rules, norms and values that apply in society. Therefore, single parents are required to work extra in carrying out activities and have a function at the same time in the family, namely acting as father, backbone of the family and as housewife. The subject used in the research was 1 student. The data collection method used was observation, interviews and documentation. By collecting qualitative data using observation, interviews and documentation. The results of this research show that the parenting style applied by a mother is democratic.